Longitudinal association of involvement and monitoring during early adolescence and empathy and value regulation during emerging adulthood - Howard, Lindsay (Kansas State University, 2024)
Emerging adulthood is a time of exploration and discovery. Many in emerging adulthood are struggling to adapt. This study seeks to understand the role of parent involvement and monitoring in early adolescence on empathy and value regulation during emerging adulthood. Using data from the Flourishing Families Project, 434 mother, father, and child triads were used to examine these associations. Parental involvement during adolescence was found to significantly predict increased empathy and value regulation in emerging adults; whereas monitoring was not found to be significantly associated with either outcome. Results highlight the important role that parent involvement, including involvement in school activities, care provided for the child, and time spent doing things with their child, has on the development of internalized values and empathy. Suggestions for how findings might guide the work of human services professionals are provided along with a discussion of how future research might expand upon this work.
Keywords: Emerging adults; Adolescence; Monitoring; Involvement; Empathy; Values